2000
DOI: 10.1074/jbc.275.14.10429
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Expression Analysis of Genes Regulated by Both Obesity and Leptin Reveals a Regulatory Loop between Leptin and Pituitary-derived ACTH

Abstract: Absence of the hormone leptin leads to dramatic increases in appetite, food intake, and adiposity. The primary site of action, at least with respect to appetite, is the hypothalamus. Leptin also has significant effects on the function(s) of peripheral organs involved in maintaining body composition. Some of these effects are mediated through direct interaction of leptin with its receptor on the target tissue, and some effects are indirectly mediated through secondary hormonal and neural pathways. Few of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…At the level of the pituitary, another study demonstrated that prolonged systemic administration of leptin increased ACTH concentrations in both adrenalectomized female rats and intact animals [30] . In contrast to these studies, chronic administration of leptin reduced POMC expression in the anterior pituitary of obese mice [35] . In rats, contrasting effects of leptin administration on steroid hormone secretion have been documented, with some studies showing a marked stimulation, and others describing a lowering effect of leptin on plasma corticosterone levels, depending on the route and duration of administration [30] .…”
Section: Leptin and The Hpa Axismentioning
confidence: 43%
“…At the level of the pituitary, another study demonstrated that prolonged systemic administration of leptin increased ACTH concentrations in both adrenalectomized female rats and intact animals [30] . In contrast to these studies, chronic administration of leptin reduced POMC expression in the anterior pituitary of obese mice [35] . In rats, contrasting effects of leptin administration on steroid hormone secretion have been documented, with some studies showing a marked stimulation, and others describing a lowering effect of leptin on plasma corticosterone levels, depending on the route and duration of administration [30] .…”
Section: Leptin and The Hpa Axismentioning
confidence: 43%
“…The generation of mature ␣MSH from POMC requires a complex pathway of posttranslational modifications involving numerous enzymes such as PC1 and PC2. Interestingly, Renz et al (29) have suggested that leptin may regulate PC2 expression in the pituitary, raising the possibility that this regulation may also occur in POMC neurons. We therefore cannot rule out that the increase in total ␣MSH in response to leptin is a result of both a stimulatory effect on pomc gene expression (13,16,25) and enhanced posttranslational processing of the POMC precursor.…”
Section: Discussionmentioning
confidence: 99%
“…This method requires no a priori gene sequence and provides Ͼ95% coverage of the expressed genome with a sensitivity of detection greater than 1:100,000 (45). GeneCalling has recently been used to identify genes linked to cardiac hypertrophy, obesity, and endothelial cell differentiation in vitro and it has been extensively confirmed by Northern blot analysis, semiquantitative RT-PCR, and real-time PCR (25,39,45).…”
Section: Adhesion To Fibronectin Through the ␣5␤1 Integrin Is Sufficimentioning
confidence: 99%